RANCANG BANGUN ANJUNGAN BIMBINGAN TUGAS AKHIR SECARA ONLINE (STUDI KASUS : JURUSAN TEKNIK INFORMATIKA STT-PLN): Dian Hartanti; Wisnu Hendro Martono - Jurnal, Redaksi Tim (PETIR, 2018)
In the process of implementation of the final task are the obstacles encountered on the initial stage of registration until the stage of completion of the final project. One form among the obstacles in the form of the registration process less effective, difficult to perform the guidance and monitoring of the implementation of the final project as well as the report of guidance do still manual. This application is designed by transform manual business processes into web and use MySQL database to store all of important data, with the order flow process similar to current manual process. In these applications, the guidance can be done remotely, the progress of implementation can be known in an instant, the valuation guidance report is organized better than before, determine the feasibility of the project that was created and the other necessary fittings, and other information that supporting the creation of final task. This application provides solution and ease of implementation final task guidance and monitoring. With this application, all activities pf prathesis running better than before. This application is implemented using PHP programming language, MySQL database and another supporting software.